2015
DOI: 10.3201/eid2110.141961
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Serosurvey of Crimean-Congo Hemorrhagic Fever Virus IgG in Livestock, India, 2013–2014

Abstract: We conducted a cross-sectional serosurvey of Crimean-Congo hemorrhagic fever (CCHF) among livestock in 22 states and 1 union territory of India. A total of 5,636 samples from bovines, sheep, and goats were screened for CCHF virus IgG. IgG was detected in 354 samples, indicating that this virus is widespread in this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
(12 reference statements)
1
26
0
Order By: Relevance
“…Furthermore, we previously conducted a countrywide, cross-sectional serosurvey that showed CCHFV is prevalent among livestock in 22 states and a union territory of India ( 9 ). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we previously conducted a countrywide, cross-sectional serosurvey that showed CCHFV is prevalent among livestock in 22 states and a union territory of India ( 9 ). …”
Section: Resultsmentioning
confidence: 99%
“…Fatal cases of CCHF in humans were confirmed in Ahmadabad in India in 2011, but a recent serosurvey in livestock showed that this disease has widespread seroprevalence in domestic animals across India ( 7 – 10 ). Bhutan shares a long, porous border with India, and animals and humans frequently cross the border.…”
mentioning
confidence: 99%
“…During October 2015, in collaboration with the National Centre for Animal Health Bhutan, we retrospectively tested serum samples collected during April–May 2015 from 81 goats and 92 cattle for CCHFV-specific IgG by using ELISA kits (Sheep/goat anti-CCHFV IgG ELISA kit and Cattle anti-CCHFV IgG ELISA kit; National Institute of Virology, Pune, India), as described ( 10 ). CCHFV IgG was detected in 31 (38.2%) goats; no cattle had positive results.…”
mentioning
confidence: 99%
“…Since its first detection, many nosocomial outbreaks and sporadic cases have been investigated and confirmed in Gujarat and the adjoining Rajasthan State, including a nosocomial outbreak in Ahmadabad, Gujarat State, in 2011 (Makwana et al, 2015; Mishra et al, 2011; Mourya et al, 2012; Yadav et al, 2013a; Yadav et al, 2016, 2014). Pragya also summarized the results of various studies, including surveys in ticks and a survey of anti-CCHFV IgG antibodies in livestock (Mourya et al, 2014a,b; Mourya et al, 2015). Animal serosurveys are considered very useful in indicating virus prevalence in an area; tick studies are less indicative, as the appropriate number of ticks that must be collected to be useful and predictive is not clear (Gurav et al, 2014; Mourya et al, 2014a,b; Mourya et al, 2015; Yadav et al, 2013b).…”
Section: Meeting Sessionsmentioning
confidence: 99%
“…Pragya also summarized the results of various studies, including surveys in ticks and a survey of anti-CCHFV IgG antibodies in livestock (Mourya et al, 2014a,b; Mourya et al, 2015). Animal serosurveys are considered very useful in indicating virus prevalence in an area; tick studies are less indicative, as the appropriate number of ticks that must be collected to be useful and predictive is not clear (Gurav et al, 2014; Mourya et al, 2014a,b; Mourya et al, 2015; Yadav et al, 2013b). …”
Section: Meeting Sessionsmentioning
confidence: 99%